Aplicação de diferentes zeólitas como catalisadores heterogêneos para a síntese de ésteres alquílicos - Dal Pozzo, Daniel Marcos (2018)
In this work the zeolites Mordenite, ZSM5, Y, Beta and Ferrierite, were employed as heterogeneous catalysts for the alkyl esters synthesis by esterification, aiming the application of these zeolites for the biodiesel production. As a model reaction to evaluate the catalytic activity of these zeolites, the esterification of oleic acid with methanol and the esterification of octanoic acid with methanol, ethanol and propanol were performed. For the reactions performed, different reaction parameters were used, such as different fatty acid:alcohol molar ratios, reaction temperatures and catalyst amounts, aiming to observe the corresponding ester conversion over time. The zeolites used were characterized by Thermogravimetry, EGA, FTIR, XRD, 27Al NMR, ED-XRF, TPD-NH3, liquid phase pyridine adsorption evaluated by FTIR, SEM and N2 adsorption/desorption. The protic form of the zeolites was obtained and the protonation range for each zeolite was visualized. The selectivity of the reactant for the zeolite H-ZSM5 was observed. Some zeolites showed catalytic activity for the alkyl esters synthesis. The catalytic activity of the zeolites did not show a clear correlation with the amount of acid sites on the material surface, but has a greater dependence on the porosity and hydrophobic balance of the material. Conversions above 85% were obtained in fatty acids esterification. Among the zeolites evaluated, the most active zeolite obtained was reused and used in several consecutive reaction cycles, where there was no decrease in the catalytic activity of the material and, in addition, the integrity of the zeolite structure was maintained. Thus, the catalytic assays allow to observe that depending on the type of zeolite used it’s possible to obtain promising results in the esterification of fatty acids, which together with the ease of separation of the zeolites from the reaction medium after the reaction and the possibility of their use in new cycles, make it interesting to use these materials for the alkyl esters synthesis.